A checklist of Stictane Hampson (Lepidoptera, Erebidae, Arctiinae) with emphasis on the Laotian fauna - Bayarsaikhan, Ulziijargal; Kwon, Hyung Wook; Kim, Kil Won; Bae, Yang-Seop (Zootaxa, 2021)
The genus Stictane Hampson is reviewed in Laos, with eight species including four newly recorded species, S. obscura (Inoue, 1976), S. pectinata Holloway, 2001, S. fuscus Bucsek, 2014 and S. bokorensis Bayarsaikhan & Bae, 2015. Illustrations of adults and genitalia of all examined species from Laos are provided, with an updated checklist of all described species of Stictane.